Security of School Financial Transaction Applications with the Implementation of Two Factor Authentication Method - Hardiansyah, Novi; Aulia, Rima; Hadriani, Angelina (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Financial transactions over the internet often become targets of cyber attacks that can harm users in conducting transactions due to negligence from both the system and human error. This research will focus on the security level of the SIKOLAH financial application, where every school financial transaction will be conducted online. In this study, the Two Factor Authentication (2FA) method will be implemented, ensuring that each user has official access with data in the database registered in the application. The results of implementing this method have successfully validated user data through verified email and WhatsApp numbers to send OTP codes to the access holder's smartphone via the official WhatsApp channel of the application manager. Avoiding server phishing actions also limits the OTP code delivery time to no more than 300 seconds to send the OTP code to users, thereby reducing the risk of data interception by cybercrime.